GIJINHOU'S ANALYSIS OF KOBAYASHI ISSA'S HAIKU (Semantic Review) - Tamara Mai Salsabila P; Yuni Masrokhah (Universitas Cokroaminoto Palopo, 2023)
In Japanese Haiku, stylistic writing is a characteristic a poet uses to express thoughts. This research aims to classify the language function of Gijinhou and describe the meaning of Gijinhou contained in Kobayashi Issa's Haiku. The novelty of this research, with previous research, is to examine the Gijinhou Language Style (Personification) in Haiku by Kobayashi Issa. This research used library search techniques to collect data and used descriptive qualitative research techniques.. The data source of this research is Kobayashi Issa's Haiku on the website haikuguy.com/issa/ totaling thirty-five data. This research uses five language functions in Kobayashi Issa's Haiku: emotive, poetic, multilingual, fatigue, and conative. And the Gijinhou language style is defined as a metaphorical language that connects inanimate items to humans and considers them humans.